2017
DOI: 10.3390/en10060772
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Energy Performance Analysis of Six Primary Photovoltaic Technologies in Madrid (Spain)

Abstract: There are a wealth of studies on photovoltaic cell technologies, however their performance in different climatic or geographies over an extended period is not completely established. The objective of this paper is to add to this area of study with an analysis of the principle photovoltaic technologies: monocrystalline silicon (mc-Si), polycrystalline silicon (pc-Si), tandem structure of amorphous silicon and microcrystalline silicon (a-Si/µc-Si tandem), cadmium telluride/cadmium sulfide (CdTe/CdS), copper-indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The value of PR is usually lesser in the summer than in the winter and is between 60 and 80% due to the losses to the PV modules caused by elevated temperature in summer (Adrada Guerra et al 2017). The PR of a given PV system and the site can be generated using PV design and simulation software applications.…”
Section: Performance Ratiomentioning
confidence: 99%
“…The value of PR is usually lesser in the summer than in the winter and is between 60 and 80% due to the losses to the PV modules caused by elevated temperature in summer (Adrada Guerra et al 2017). The PR of a given PV system and the site can be generated using PV design and simulation software applications.…”
Section: Performance Ratiomentioning
confidence: 99%
“…Moreover, this method is used in different works [51][52][53][54]. PR for conventional photovoltaic systems may be typically in a range from 0.70 to 0.80 in Spain [55]. In this paper, PR values of 0.75 will be considered, based on the experience of this kind of system [56][57][58][59][60].…”
Section: The Photovoltaic Generation Profilementioning
confidence: 99%
“…Cadmium Telluride (CdTe) has long been a prominent material in thin film solar cell production due to its near-perfect bandgap (Eg = 1.45 eV) and good optical absorption coefficient of 5.10 5 cm -1 [9]. Moreover, the power temperature coefficient, which represents the power drop caused by the increase of cells temperature above the STC value (25°C), is ~ -0.25%/°C for the CdTe [10] while it is much higher for the c-Si with values around -0.45%/°C [11], [12]. Several studies reported that temperature is a crucial parameter that negatively affect the performance of solar panels [13]- [15].…”
Section: Introductionmentioning
confidence: 99%